Fiziol Zh 2013
DOI: 10.15407/fz59.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic effect of probiotic strains Bifidobacterium animalis VKL and VKB on stress-induced lesions in the gastric mucosa of rats

Abstract: Профілактична дія пробіотичних штамів Bifidobacterium animalis VKL і VKB на стресіндуковані ураження в слизовій оболонці шлунка щурів Вивчали вплив пробіотичних штамів Bifidobacterium animalis VKL і VKB та їхньої суміші на ерозивно-виразкові ураження слизової оболонки шлунка щурів (СОШ), викликані водно-іммобілізаційним стресом. Встановлено, що окреме профілактичне введення впродовж 14 діб штамів Bifidobacterium animalis VKL і VKB не впливало на ураженість СОШ, викликану стресом. Проте профілактичне введення ї… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…The studies concerning the roles of probiotics in gastric ulcer healing reported in the literature were mainly conducted in rats. These studies were based on the use of either individual probiotic strains, such as Lactobacillus rhamnosus GG ( 42 , 48 ), Lactobacillus gasseri OLL2716 ( 44 ), Lactobacillus acidophilus ( 45 , 46 ), Escherichia coli Nissle 1917 ( 114 ), Bifidobacterium animalis VKL/VKB ( 115 ), Bifidobacterium bifidum / brevis ( 116 ) and Saccharomyces boulardii ( 51 ), or a mixture of probiotic strains, such as VSL#3 ( 47 ). A number of studies have reported that probiotics not only inhibit the development of acute gastric mucosal lesions, but also accelerate the process of healing of induced gastric ulcers ( 42 , 44 , 47 ).…”
Section: Prophylactic and Therapeutic Effects Of Probiotics In Gastrimentioning
confidence: 99%
See 2 more Smart Citations
“…The studies concerning the roles of probiotics in gastric ulcer healing reported in the literature were mainly conducted in rats. These studies were based on the use of either individual probiotic strains, such as Lactobacillus rhamnosus GG ( 42 , 48 ), Lactobacillus gasseri OLL2716 ( 44 ), Lactobacillus acidophilus ( 45 , 46 ), Escherichia coli Nissle 1917 ( 114 ), Bifidobacterium animalis VKL/VKB ( 115 ), Bifidobacterium bifidum / brevis ( 116 ) and Saccharomyces boulardii ( 51 ), or a mixture of probiotic strains, such as VSL#3 ( 47 ). A number of studies have reported that probiotics not only inhibit the development of acute gastric mucosal lesions, but also accelerate the process of healing of induced gastric ulcers ( 42 , 44 , 47 ).…”
Section: Prophylactic and Therapeutic Effects Of Probiotics In Gastrimentioning
confidence: 99%
“…Probiotics can also protect the integrity of the gastric mucosal barrier by upregulating prostaglandin, mucous secretion, tight junction protein expression and cell proliferation, and by inhibiting apoptosis ( 43 , 48 , 130 132 ). In rats, the administration of Bifidobacterium bifidum BF-1 or Bifidobacterium animalis VKL and VKB has been found to protect the gastric mucosa through either preventing the mucous barrier from degradation ( 115 ) or increasing gastric mucous production ( 133 ). The probiotic mixture VSL#3 protects the epithelial barrier and upregulates the expression of tight junction proteins (occludin and zonula occludens-1) in vivo and in vitro via the activation of p38 or mitogen-activated protein (MAP) kinase and extracellular signal-regulated kinase (ERK) signaling pathways ( 134 ).…”
Section: Prophylactic and Therapeutic Effects Of Probiotics In Gastrimentioning
confidence: 99%
See 1 more Smart Citation
“…Для оцінки біодоступності на підставі експериментальних даних з виз начення концентрації у біологічних рідинах використовують різні фармакокінетичні моделі -як класичні камерні, так й від носно нові, перфузійні (що враховують кровообіг в органі, показники метаболізму, інші фізіологічні параметри [2,3]). Також приділяється увага впливу різних фізіологічних факторів на функціональний стан шлунково-кишкової системи [4,5].…”
Section: вступunclassified